POST MORTEM PROTECTION OF PERSONALITY RIGHTS IN THE TECHNOLOGICAL SOCIETY - Lima, Manuela Ithamar; de Souza Junior, Joaquim Ribeiro (Seven Editora, 2026)
This article is based on the following research question: to what extent is the post mortem protection of personality rights affected in a technological society? To address this question, the article is divided into two parts. The first presents an overview of Post mortem protection in Brazil, and the second explores the controversies surrounding such protection in a technological society. The methodological approach is deductive, and the research techniques employed are exploratory and bibliographic. DOI: https://doi.org/10.56238/sevened2026.008-115